2021
DOI: 10.1523/jneurosci.2121-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

NOX1/NADPH Oxidase Promotes Synaptic Facilitation Induced by Repeated D2Receptor Stimulation: Involvement in Behavioral Repetition

Abstract: Repetitive behavior is a widely observed neuropsychiatric symptom. Abnormal dopaminergic signaling in the striatum is one of the factors associated with behavioral repetition; however, the molecular mechanisms underlying the induction of repetitive behavior remain unclear. Here, we demonstrated that the NOX1 isoform of the superoxide-producing enzyme NADPH oxidase regulated repetitive behavior in mice by facilitating excitatory synaptic inputs in the central striatum (CS). In male C57Bl/6J mice, repeated stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…a decrease in the binding availability of striatal D 2 R [ 11 ]) have been reported in patients with primary OCD, there may be pathological similarities between patients with primary OCD and medication-induced OCD-like symptoms, especially dopaminergic abnormalities. Consistent with this postulation, we found that repeated administration of a D 2 R agonist (quinpirole; QNP) induced OCD-like repetitive and perseverative behaviours in mice [ 12 , 13 ]. This finding demonstrates a common therapeutic strategy for primary OCD and medication-induced OCD-like symptoms.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…a decrease in the binding availability of striatal D 2 R [ 11 ]) have been reported in patients with primary OCD, there may be pathological similarities between patients with primary OCD and medication-induced OCD-like symptoms, especially dopaminergic abnormalities. Consistent with this postulation, we found that repeated administration of a D 2 R agonist (quinpirole; QNP) induced OCD-like repetitive and perseverative behaviours in mice [ 12 , 13 ]. This finding demonstrates a common therapeutic strategy for primary OCD and medication-induced OCD-like symptoms.…”
Section: Introductionmentioning
confidence: 54%
“…Repeated injections of a D 2 R agonist (QNP) elicit OCD-like behavioural and neurological abnormalities in mice [ 12 , 13 , 17 ]. We assessed the effects of PPIs on QNP-induced OCD-like behaviours to obtain preclinical proof-of-concept.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations